2006
DOI: 10.1002/ana.20899
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis in the anticonvulsant mechanism of the ketogenic diet

Abstract: These data show that a calorie-restricted KD enhances brain metabolism. We propose an anticonvulsant mechanism of the KD involving mitochondrial biogenesis leading to enhanced alternative energy stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
454
1
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(483 citation statements)
references
References 70 publications
20
454
1
8
Order By: Relevance
“…The equilibrium of the transamination reaction toward oxaloacetate in the presence of increased α-ketoglutarate implies that availability of glutamate will be enhanced. Total brain glutamate is not increased by the ketogenic diet [38,39], although there may be small regional increases [40]. Radiotracer study has demonstrated increased synthesis of glutamate in ketotic mice consuming a ketogenic diet [38].…”
Section: Effects Of the Ketogenic Diet On Gaba Synthesismentioning
confidence: 98%
See 2 more Smart Citations
“…The equilibrium of the transamination reaction toward oxaloacetate in the presence of increased α-ketoglutarate implies that availability of glutamate will be enhanced. Total brain glutamate is not increased by the ketogenic diet [38,39], although there may be small regional increases [40]. Radiotracer study has demonstrated increased synthesis of glutamate in ketotic mice consuming a ketogenic diet [38].…”
Section: Effects Of the Ketogenic Diet On Gaba Synthesismentioning
confidence: 98%
“…2). The shift in this transamination reaction would be expected to reduce aspartate, and substantial (23%) decreases in whole brain aspartate levels have been observed in mice receiving a ketogenic diet for 3 days [38], although this is not a consistent finding [39]. Anticonvulsant effects of the diet are not seen until after 7 to 10 days in rodents [42,58].…”
Section: Excitatory Amino Acid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,13,14 The protective effect of KB has been mostly attributed to their conversion to AcetylCoA improving mitochondrial metabolism and preserving energy levels. [15][16][17] However, studies suggest that besides providing energy to neurons, KB reduce the production of reactive oxygen species (ROS) contributing to their protective effect. It has been observed in vitro that AcAc reduces ROS levels induced by glutamate exposure and glycolysis inhibition in cultured neurons, 12,16 and previous in vivo studies have shown that BHB decreases hypoglycemia and glutamate-mediated lipoperoxidation in the rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…Bough et al 15 have reported that rats on the ketogenic diet produce more mitochondria than rats on normal rodent chow. Presumably, more mitochondria would also mean more energy for the brain, and, therefore, possibly, fewer seizures.…”
Section: Increase In Mitochondrial Numbermentioning
confidence: 99%